2012
DOI: 10.3389/fnana.2012.00001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum: links between development, developmental disorders and motor learning

Abstract: The study of the links and interactions between development and motor learning has noticeable implications for the understanding and management of neurodevelopmental disorders. This is particularly relevant for the cerebellum which is critical for sensorimotor learning. The olivocerebellar pathway is a key pathway contributing to learning of motor skills. Its developmental maturation and remodeling are being unraveled. Advances in genetics have led to major improvements in our appraisal of the genes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 92 publications
(119 reference statements)
6
102
0
Order By: Relevance
“…In mammals, the gene En2 is involved in cerebellar patterning from early to late developmental stages, including specification of cerebellar cell types and numbers, and cerebellar morphogenesis [Kuemerle et al, 1997;Cheng et al, 2010;Wilson et al, 2011;Manto and Jissendi, 2012]. The ortholog gene ScEn2 is expressed in a subset of CN cells (present results) and in the cerebellar cortex, which supports its involvement in the development of the shark cerebellum [Pose-Méndez et al, 2016b].…”
Section: Evolutionary and Developmental Analysissupporting
confidence: 64%
See 1 more Smart Citation
“…In mammals, the gene En2 is involved in cerebellar patterning from early to late developmental stages, including specification of cerebellar cell types and numbers, and cerebellar morphogenesis [Kuemerle et al, 1997;Cheng et al, 2010;Wilson et al, 2011;Manto and Jissendi, 2012]. The ortholog gene ScEn2 is expressed in a subset of CN cells (present results) and in the cerebellar cortex, which supports its involvement in the development of the shark cerebellum [Pose-Méndez et al, 2016b].…”
Section: Evolutionary and Developmental Analysissupporting
confidence: 64%
“…3e). Further characterization of subpopulations in the S. canicula CN was obtained analyzing the expression pattern of En2, a member of the engrailed (En) homeobox transcription factor family that is critical for patterning of the cerebellum in mammals [Manto and Jissendi, 2012]. In the CN of S. canicula, ScEn2 was expressed in cells of the inner medial region (Fig.…”
Section: Expression Pattern Of Cerebellar Nucleus Cell Markers In Thementioning
confidence: 99%
“…However, the VNS is linked via development, neural connectivity and functional overlap to the MOS, and findings in the MOS may apply to other chemosensory systems. The concept of absolute separation between the two systems has been overturned; both can detect general odorants and pheromones (Spehr et al, 2006; Keller et al, 2009), and the respective central projections are highly interconnected (Mucignat‐Caretta et al, 2012). Martínez‐García et al (2009) suggested that MOS and VNS are complementary, the MOS detecting volatile stimuli related to diet, activity pattern, habitat, navigation and sociosexual signals (Jacobs, 2012), and VNS detecting nonvolatile stimuli for sociosexual behavior and predator avoidance (Døving and Trotier, 1998; Fortes‐Marco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research in rodents suggests that morphine treatment has a negative effect on the development of cerebellar neurons. 11 A study in human preterm-born infants 17 found that they were more at risk for cerebellar injuries during the neonatal period than were term-born infants and that at adolescent age their cerebellum volume was smaller than that in term-born adolescents. The minor neurological dysfunctions observed may reflect the combined consequences of prematurity and critical illness along with potential effects of morphine, not the effects of morphine in isolation.…”
Section: Neurological Functioningmentioning
confidence: 98%